2010
DOI: 10.1097/jto.0b013e3181e15d33
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemotherapy and Short Course Radiotherapy in Patients with Stage IIIA to IIIB Non-small Cell Lung Cancer Not Eligible for Radical Treatment: Results of a Randomized Phase II Study

Abstract: Upfront chemotherapy combined with palliative radiotherapy (30 Gy) is a promising treatment option in the subpopulation of patients with stage IIIA to IIIB NSCLC not amenable for definitive chemoradiotherapy and deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…Secondly, except for PS of ECOG 2 and weight loss ≥5% (n = 27), our enrolled patients had no other poor prognostic factors. As a result, the prognosis of ECOG 2 patients in our study was more favorable than that of the poor risk patients enrolled in other clinical trials [13,14,17,18,20]. Thirdly, our CCRT intensity including RT dose and chemotherapy regimen was more aggressive than that administered for poor risk patients with palliative intent [17,18].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Secondly, except for PS of ECOG 2 and weight loss ≥5% (n = 27), our enrolled patients had no other poor prognostic factors. As a result, the prognosis of ECOG 2 patients in our study was more favorable than that of the poor risk patients enrolled in other clinical trials [13,14,17,18,20]. Thirdly, our CCRT intensity including RT dose and chemotherapy regimen was more aggressive than that administered for poor risk patients with palliative intent [17,18].…”
Section: Discussionmentioning
confidence: 69%
“…Based on the encouraging outcome achieved in the above single arm phase II trials, many clinical trials have investigated whether CCRT is superior to radiotherapy alone or chemotherapy alone for poor risk stage III NSCLC. Nawrocki et al [17] conducted a phase II study which randomly assigned poorrisk stage III NSCLC to either radiation alone of palliative dose (30Gy) or the same radiation dose delivered concurrently with the third of 3 cycles of cisplatin/vinorelbine. Three-dimensional conformal planning was used.…”
Section: Discussionmentioning
confidence: 99%
“…This regimen was well tolerated and yielded a median survival comparable to that of patients with better prognosis who received cisplatin-based chemoradiotherapy. In a recent randomised phase II study, Nawrocki et al (2010) concluded that upfront chemotherapy combined with palliative radiotherapy (30 Gy/10 fractions) resulted in superior response rates and survival when compared with radiotherapy alone in patients with stage III locally advanced NSCLC and poor prognostic factors (tumours >8 cm and/or poor pulmonary reserve, performance status 0–2, tumour-related chest symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…W latach 2003-2006 w SP ZOZ MSW z W-MCO w Olsztynie leczono napromienianiem 801 pacjentów chorych na NDRP. 81 pacjentów (10% wszystkich analizowanych) było leczonych w ramach randomizowanego badania klinicznego II fazy "Concurrent chemotherapy and short course radiotherapy in patients with stage IIIA to IIIB non-small cell lung cancer not eligible for radical treatment" [6] (tab. I).…”
Section: Wynikiunclassified
“…Statystyczne porównanie tych grup jest więc niemożliwe. Wcześniej opublikowane wyniki badania z randomizacją przeprowadzonego w tutejszym ośrodku dla grupy chorych z rozpoznaniem NSCLC w stopniu zaawansowania klinicznego IIIA i IIIB niekwalifikujących się do leczenia radykalnego wykazały lepsze 2-letnie OS pacjentów poddanych paliatywnej jednoczasowej radiochemioterapii w stosunku do pacjentów poddanych samodzielnej radioterapii (10 frakcji w dawce frakcyjnej 3 Gy), odpowiednio 24% vs 6% [6]. Pięcioletnie przeżycia pacjentów, którzy otrzymali radiochemioterapię, wyniosły 9%.…”
Section: Dyskusjaunclassified